Using UML for learning how to design and model cyber-physical systems - Ordinez, Leonardo Damian (2020)
In this paper a methodology for teaching and learn-ing the modeling of embedded systems and, in a more genericvision cyber-physical systems (CPS) is presented. To this end, asubset of tools from UML is used in an intuitive and orderedway starting with an informal description of the system untilimplementation details are obtained. However, the codificationof the system is left out as the programming language dependson the hardware platform to be used. The method has beenused in grade courses for several years now with an importantaccumulated experience that shows how students are able toadopt it and learn to elicit the different types of requirements,actors and functions.